Pemanfaatan Media Sosial Sebagai Wadah Usaha Pakaian Bekas di Pajak Melati Kota Medan: Studi Kasus pada Aplikasi Tiktok - Ridho Ananda Purba; Husni Ritonga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The case study of selling used clothes at Tax Melati Tj. Anom is the subject of this research, which aims to find out how social media influences the sales turnover of Monza MSMEs. This study looked at Monza MSME traders. Used clothing is still often considered taboo by some people because it has a negative impact, so not many people use it. Used clothing is increasingly popular with the presence of 'garage sales' from second-hand clothing stores or online stores. In this research, the author explains that there are factors behind online traders of second-hand clothing using jasmine tax in using social media Tiktok. This research also explains how the people of Medan interpret the use of used clothing. This research uses qualitative research using a phenomenological method approach. The data collection techniques used in this article are interviews, observation and documentation supported by primary and secondary data. The results of this research show that used clothing buyers in the jasmine tax interpret the use of used clothing as a lifestyle and fashion trend. They choose used clothes because they are affordable, well-known brands, unique, limited edition, quality materials, add to their clothing collection and look fashionable. In using second-hand clothes, they are influenced by the family and social environment, the existence of second-hand clothing shops and the mass media. Used clothing has become an object that the people of Medan are looking for to fulfill their clothing needs and as part of their lifestyle.